Audio power amplifier design handbook - Self, Douglas
Douglas Self offers a tried and tested method for designing audio amplifiers in a way that improves performance at every point in the circuit where distortion can creep in without significantly increasing cost. His quest for the Blameless Amplifier takes readers through the causes of distortion, measurement techniques, and design solutions to minimise distortion and efficiency. The result is a book that is crammed with unique insights into audio design and performance, as well as complete amplifier designs and schematics. Whether you are a dedicated audiophile who wants to gain a more complete understanding of the design issues behind a truly great amp, or a professional electronic designer seeking to learn more about the art of amplifier design, Douglas Selfs Handbook is the essential guide to design principles and practice. Self is senior designer with a high-end audio manufacturer, as well as author of numerous magazine articles in the pages of Electronics World / Wireless World. His career in audio design is the foundation of a book that is based solidly on practical experience as well as a dedication to a methodology based on measurement, analysis and scientific design principles. The fourth edition includes new material on DC offset protection circuitry, the design of DC servos and electrical safety and safety standards. In addition, there is a new chapter on Class D power amplifiers. EPS files for selected figures are available at http://books.elsevier.com/companions/9780750680721 * The definitive guide to understanding and designing audio amplifiers * Includes Douglas Self's classic amp designs for readers to build and adapt * A classic work for electronics enthusiasts, Hi-Fi devotees and professional designers alike.